TRAGIC IN NON-SATIRICAL PROSE OF RADOJE DOMANOVIĆ - Soleša, Biljana S (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
This paper explores tragic elements in Radoje Domanović’s short stories. Firstly, it stipulates the possible approaches to the interpretation of the phenomenon of tragic in literary works, with particular review of tragic as aesthetic and ethical phenomenon, as well as of the manner in which the tragic is shown in literary works. In the central part it describes basic characteristics of Domanović's non-satirical prose. The exploration of tragic elements included the short stories A hleba...?!, Smrt, Razorena sreća, Promašena sreća, Idealista, Pevačev Uskrs, Na raskršću. The interpretation of short stories in which the elements of tragic were most visible singled out the most frequent patterns: active actions, conscious sacrifice, suffering without guilt, excessiveness and conflict of values. The final part points out the importance of exploring the phenomenon of tragic in Domanović’s works and literature.
Keywords: tragic; GUILT; stories; prose; phenomenon; elements